Change in the incidence and anatomic distribution of colorectal adenoma and cancer over a period of 20 years – A single center experience - Alempijevic, Tamara; Nikolic, Vladimir; Zec, Simon; Veljkovic, Aleksandar; Sokic-Milutinovic, Aleksandra; Pavlovic-Markovic, Aleksandra; Matovic, Vera; Popovic, Dusan Dj; Milosavljevic, Tomica (Vojnosanitetski pregled, 2020)
Background/Aim. In recent years, many studies have demonstrated a proximal shift in the distribution of adenomas and colorectal cancers. The aim of this study was to investigate whether there are differences in the incidence and anatomical distribution of adenomas and colorectal cancers spanning a 20 year time gap. Methods. We performed a retrospective observational study of colorectal adenomas and cancers diagnosed during total colonoscopy in a high volume tertiary care facility in two 1-year periods of time – 1990 and 2010. Results. During the analyzed period, 4,048 colonoscopies were performed, 1,148 were performed in 1990 and 2,900 were done in 2010. The study included 466 patients with adenomas and 121 patients with colorectal cancers. Frequency of proximal adenoma changed from 16.5% to 32.7% (p < 0.001). By analyzing colonoscopies in 2010, an increase in the incidence of adenomas compared to 1990 was noticed. The number of adenomas sized 0–5 mm rose from 32.8% to 56.9% (p < 0.001). Frequency of colon carcinoma changed from 5.3% to 2.0% (p < 0.001). Incidence of cancers in the proximal colon rose from 21.3% to 48.4% (p = 0.002). A higher incidence of cancers in the proximal colon and a lower incidence of distal cancers were observed, while no difference was observed in the incidence of rectal cancers. Conclusion. Presence of proximal colon adenoma and cancer is higher, while the overall incidence of colon cancer is lower. This finding should be taken into account when planning the screening for colorectal cancer.